2022
DOI: 10.1007/s40263-022-00934-0
|View full text |Cite
|
Sign up to set email alerts
|

The Purinergic System as a Target for the Development of Treatments for Bipolar Disorder

Abstract: The neurobiological and neurochemical mechanisms underlying the pathophysiology of bipolar disorder are complex and not yet fully understood. From circadian disruption to neuroinflammation, many pathways and signaling molecules are important contributors to bipolar disorder development, some specific to a disease subtype or a cycling episode. Pharmacological agents for bipolar disorder have shown only partial efficacy, including mood stabilizers and antipsychotics. The purinergic hypothesis for bipolar disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 183 publications
0
5
0
Order By: Relevance
“…Extracellular ATP acts on purinergic receptors P2X (P2XR) and P2Y (P2YR), activating several intracellular signaling cascades. ATP is metabolized into ADP, adenosine 5′-monophosphate (AMP), and adenosine by ectoenzymes that directly regulate extracellular purine concentrations ( Gonçalves et al, 2022 ). While only limited clinical data are available, extensive basic and preclinical research supports the importance of adenosine and the purinergic system in the pathophysiology of BD.…”
Section: The Purinergic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular ATP acts on purinergic receptors P2X (P2XR) and P2Y (P2YR), activating several intracellular signaling cascades. ATP is metabolized into ADP, adenosine 5′-monophosphate (AMP), and adenosine by ectoenzymes that directly regulate extracellular purine concentrations ( Gonçalves et al, 2022 ). While only limited clinical data are available, extensive basic and preclinical research supports the importance of adenosine and the purinergic system in the pathophysiology of BD.…”
Section: The Purinergic Systemmentioning
confidence: 99%
“…As a result, targeted therapies for P2X7 in BD and MDD are currently being developed and tested. In animal models of mania—predominantly the amphetamine-induced hyperactive locomotion model—P2X7R antagonism was found to be a promising therapeutic candidate for BD ( Gonçalves et al, 2022 ). Indeed, that study hypothesized that next-generation P2X7R antagonists are the most promising adjunctive therapy or monotherapy for BD and related disorders that affect the CNS.…”
Section: The Purinergic Systemmentioning
confidence: 99%
“…Patients with mania have elevated uric acid levels, which may indicate the dysfunction of the purinergic system. 15 , 16 , 17 Purinergic signaling is mediated by specific purinergic membrane receptors activated by extracellularly released nucleosides (P1 adenosine receptors) and nucleotides (P2Y and P2X receptors). The homomeric P2X7R is a unique member of the ATP-gated ionotropic P2X receptor family with low ATP affinity.…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 24 It is well known that P2X7R activation regulates the expression of proinflammatory cytokines such as IL-6, TNF-α, and IL-1β, and the latter may be associated with the antimanic effect of P2X7R inhibition. 17 , 28 , 29 In peripheral and central immune cells, ATP-activated P2X7R promotes the NLRP3 (NOD-like receptor protein 3) inflammasome-mediated activation of caspase-1 and leads to IL-1β secretion 30 , 31 following priming stimulus. Therefore, the possibility arises that IL-1β is also involved in ameliorating the effect of P2X7R inhibition on manic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the purine system is associated with a variety of neuropsychiatric disorders [19], including disturbance of sleep [20], anhedonia [21],a drop in energy, cognitive impairment [22], and psychomotor agitation [23]. People with high SUA are more likely to have elevated drive and impulsivity, even if they can't reach a psychiatric diagnosis [24].…”
Section: Introductionmentioning
confidence: 99%